AB0190 Patients with Antiphospholipid Antibodies and Recurrent Pregnancy Loss: 3' Untranslated Region (3'UTR) Polymorphisms of the HLA-G Gene as A Possible Link between Innate Immunology and Autoimmunity. (10th June 2014) - Canti, V.; Amodio, G.; Castiglioni, M.; Maggio, L.; Gregori, S.; Rovere-Querini, P.
Abstract : Background: Recurrent pregnancy loss (RPL) occurs in 2-4% of fertile couples. The cause of the miscarriages remains in half of the cases unknown. A defective establishment of immune tolerance towards fetal antigens might be involved. HLA-G is a non-classical class I HLA molecule, which is preferentially expressed by extravillous trophoblast cells at the maternal-fetal interface. Polymorphism of the coding sequence of the HLA-G gene is limited. In contrast, the noncoding 3' untranslated region (3'UTR) of the gene is highly polymorphic and 14bp ins/del polymorphism plays an important role in the post-transcriptional regulation of HLA-G expression and might influence its function. Objectives: To analyze whether 3'UTR HLAG polymorphisms might be associated with RPL in patients with or without antiphospholipid antibodies (aPL). Methods: Blood samples and clinical data were collected from 132 healthy donors and 65 women with RPL (defined as two of more consecutive miscarriages), prospectively followed at the "Pathologic Pregnancy Unit" outpatient clinic of San Raffaele Hospital, Milan, Italy from 2002 to 2012 during a further pregnancy. We evaluated and comparatively studied the insertion(+) or deletion(−) of 14 bp in the 3'UTR and the association between 3'UTR haplotypes of HLA-G and the presence(aPL-pos) or absence(aPL-neg) of aPL(anticardiolipin, anti beta2 glycoprotein IgG and IgM or LLAC). Genetic and serological data were correlated with the pregnancy outcomes. Results: A heterozygous genotype(+/−) was detected in 58.8% (30/51) aPL-neg RPL patients versus 42.9% (6/14) aPL-pos patients; 25.5% (13/51) aPL-neg versus 35.7% (5/14) aPL-pos had a homozygous deletion genotype(−/−); 15.7% (8/51) aPL-neg versus 21.4% (3/14) aPL-pos had a homozygous insertion(+/+). In the control group 47.7% of the subjects (63/132) were (+/−), 30.4% (40/132) were (−/−) and 21.9% (29/132) were (+/+). The frequency of the UTR-8(−/−) haplotype in healthy donors was significantly lower than in patients (6.8%; 9/132: p<0.05). In contrast, we did not observe any significant association between the clinical phenotype and any other HLA-G haplotype. We are currently evaluating whether the presence of the UTR-8 haplotype is associated with the pregnancy outcomes in aPL-pos and aPL-neg patients. Preliminary data on a little group of aPL-pos-UTR-8 haplotype show a higher incidence of RPL (66.7%, 2/3) than in aPL-pos-UTR-different haplotype (20%, 2/10). Conclusions: The non-coding 3'UTR HLA-G region is significantly more frequent in RPL women when compared with the control group. The possible influence of this finding on the pathogenic potential of aPL in pregnancy is being investigated. References: Wang X. et al;Tissue Antigens. 2013 Shankarkumar U. et al; J Hum Reprod Sci. 2011 Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4307